A multi-step-ahead prediction model fusing spatial information transformation and synchronous error correction in wastewater treatment plants - Dong Li; Pedram Ramin; Haiwu Yu; Feng Li; Yiqi Liu; Lining Xing (Journal of Water Process Engineering, 2026)

Immune Efficacy and Intestinal Microbiota of Rainbow Trout ( Oncorhynchus mykiss ) After Inactivated IHNV Vaccination via Distinct Injection Regimens - Zhiyuan Luo; Jie Li; Caixia Shan; Yu Ning; Yanyan Luo; Mingzhou Zhang; Wenwen Zhang; Lining Ren; Zhe Liu; Jianfu Wang (Journal of Fish Diseases, 2026)
This study optimised the immunisation protocol for rainbow trout fingerlings against infectious haematopoietic necrosis virus (IHNV). Fish were administered an experimental vaccine via intraperitoneal injection, consisting of formalin‐inactivated IHNV formulated with Montanide ISA 763A VG. A 2 × 2 factorial design was employed to compare two injection volumes (50 μL or 150 μL) and two immunisation regimens (single versus double injection). Serum neutralising antibody titres, splenic expression of six immune‐related genes ( TLR7 , MyD88 , IRF7 , IFN‐α , IgM , Mx‐1 ), and gut microbiota composition were assessed before and after IHNV challenge. A double immunisation regimen with 50 μL elicited the highest antibody titres and the most robust post‐challenge upregulation of all target genes, whereas administration of 150 μL alone yielded inferior outcomes. 16S rRNA gene sequencing revealed Proteobacteria and Cyanobacteria as the predominant bacterial phyla across all treatment groups. Immunisation significantly reduced the abundance of potentially pathogenic taxa (e.g., Flavobacterium , Vibrio ) and increased that of Pseudomonas and Acinetobacter , indicating enhanced intestinal homeostasis and antiviral gene expression. Collectively, a two‐dose regimen with 50 μL maximises systemic immunity, strengthens mucosal defence and supports a balanced gut microbiota, providing a practical and effective strategy for IHNV control in rainbow trout aquaculture.

Separation and cyclic enrichment of valuable elements (Ga, Ge, In) from Zn vacuum smelting slag by stepwise leaching with sulfuric and acetic acid - Huazhen Cao; Canjiang Li; Junfeng Kong; Lining Yu; Anyang Tang; Jingnan Zheng; Zhengzheng Liu; Huibin Zhang; Guoqu Zheng (Hydrometallurgy, 2026)

Multi-objective optimization for integrated energy systems using non-dominated sorting genetic and swarm intelligence methods - Feng Li; Yonghui Chen; Ying Hu; Yang Yu; Lining Xing (Swarm and Evolutionary Computation, 2026)

A reinforcement learning-based artificial bee colony algorithm for resolving the UAV logistics path planning problem in a 3D space - Runkai Liu; Wei Hu; Witold Pedrycz; Yanjie Song; Lining Xing; Yongguang Yu (Swarm and Evolutionary Computation, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Effects of a recombinant IHNV glycoprotein vaccine on intestinal mucosal immunity and microbiota structure in rainbow trout (Oncorhynchus mykiss) - Yanyan Luo; Jianfu Wang; Yu Ning; Hao Liu; Zhiyuan Luo; Jie Li; Mingzhou Zhang; Wenwen Zhang; Lining Ren (Aquaculture International, 2026)

A thermodynamic and kinetic study of efficient selenium removal from highly acidic TeCl4 solution using tellurium powder - Wenqiu Wang; Huazhen Cao; Weilun Qian; Anyang Tang; Junfeng Kong; Lining Yu; Zhengzheng Liu; Huibin Zhang; Guoqu Zheng (Hydrometallurgy, 2025)

The impact of natural organic matter on the aggregation, dissolution and sedimentation of cadmium telluride quantum dots and their interacting mechanism - Jing Wang; Pengxiang Zhu; Meiyu Li; Rui Lu; Xinping Yu; Lezun Wang; Lining Zhao (Environmental Research, 2025)

Sustainable large-scale hyper-enrichment of gold via ferrous sulfide-mediated sulfuric acid leaching - Weilun Qian; Zhengzheng Liu; Anyang Tang; Junfeng Kong; Lining Yu; Wenyu Feng; Huibin Zhang; Huazhen Cao; Guoqu Zheng (Journal of Cleaner Production, 2025)

Improving synergistic catalysis of CuOx/AgOy/TiO2 for promoting selective catalytic oxidation of ammonia - Junfei Chen; Zhihao Yu; Jinwei Wu; Zhao-Bin Ding; Lin Lang; Lining Fang; Xiuli Yin; Zebao Rui (Chemical Engineering Journal, 2025)

Assessing the ecological effects of the World’s Largest Forestry Eco-engineering: Three-North Protective Forest Program within the initially scheduled range from 1978 to 2022 - Xiao Zheng; Jiaojun Zhu; G. Geoff Wang; Qiaoling Yan; Tao Sun; Lining Song; Tian Gao; Yirong Sun; Xiufen Li; Kai Yang; Jinxin Zhang; Lizhong Yu; et al. (Science China Life Sciences, 2025)

Development of a Csy4-Processing TRV-Based CRISPR/Cas9 Genome Editing System in Nicotiana benthamiana - Yanjie Luo; Xiaodong Tang; Cuihong Yu; Yang Qiu; Julia S. Nowak; Qing Shi Lu; Lining Tian; Ren Na (Plant Molecular Biology Reporter, 2024)
The CRISPR/Cas9 system is a site-specific genome editing tool that has been widely used in various plant species. The plant virus-based gRNA (guide RNA) delivery system, which differs from the typical Agrobacterium -mediated transformation, is an attractive method to facilitate the application of CRISPR/Cas9. The virally delivered gRNA is usually driven by heterologous plant U6 or viral promoters (e.g., pea early-browning virus, PEBV; barley stripe mosaic virus, BSMV). However, heterologous promoters may have poor performance in some cases. In this paper, a feasible option to detach gRNA(s) from the virus genome is employed. Specifically, the Csy4-RNA processing system is used to release gRNA(s) from the tobacco rattle virus (TRV). The coding sequences of Cas9 and Csy4 nucleases are cloned into a single polycistronic expression cassette under an estrogen-inducible promoter in a binary vector, and the gRNA is cloned into the TRV genome flanked by two 20 bp Csy4 recognition sites. The results show that the Csy4-processing TRV-based delivery system works effectively in targeting single and multiple sites, nucleotide replacement, and large fragment deletion in Cas9-mediated genome editing via transient expression in Nicotiana benthamiana . The Csy4-TRV is a promising gRNA(s) processing and delivery system for CRISPR/Cas9 genome editing. This method can be easily adapted to other plant RNA viruses, facilitating the application of the CRISPR/Cas9 system in plants.

Lead removal from tin chloride solution by barium sulfate and coprecipitation of (BaxPby)(SO4)2 for the processing of Pb Sn smelter slag - Lining Yu; Huazhen Cao; Huibin Zhang; Junfeng Kong; Weilun Qian; Anyang Tang; Wenyu Feng; Guoqu Zheng (Hydrometallurgy, 2024)

Deep removal of trace arsenic from acidic SbCl3 solution by in-situ galvanically coupled Cu2Sb/Cu particles - Junfeng Kong; Huazhen Cao; Weilun Qian; Lining Yu; Anyang Tang; Wenyu Feng; Huibin Zhang; Guoqu Zheng (Journal of Hazardous Materials, 2024)

Ordered heterostructured aerogel for multi-spectra stealth in microwave, infrared and visible light bands - Yu Gao; Qiang Wu; Lining Pan; Xueheng Zhuang; Feng Tian; Xingjie Jia; Qikui Man; Baogen Shen (Chemical Engineering Journal, 2024)

A computational network dynamical modeling for abnormal oscillation and deep brain stimulation control of obsessive–compulsive disorder - Lining Yin; Fang Han; Ying Yu; Qingyun Wang (Cognitive Neurodynamics, 2023)

Exposure to outdoor artificial light at night increases risk and burden of metabolic disease in Ningxia, China - Huihui Wang; Xiaohong Ma; Zhenfan Yu; Naifan Hu; Yurun Du; Xiaoxue He; Degong Pan; Lining Pu; Xue Zhang; Xian Sun; Jiangping Li (Environmental Science and Pollution Research, 2023)

The potential meat flavoring generated from Maillard reaction products of wheat gluten protein hydrolysates-xylose: Impacts of different thermal treatment temperatures on flavor - Ao Sun; Lining Chen; Wei Wu; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Food Research International, 2023)

Lightweight chitosan-derived carbon/rGO aerogels loaded with hollow Co1-Ni O nanocubes for superior electromagnetic wave absorption and heat insulation - Yu Gao; Zhenkuang Lei; Lining Pan; Qiang Wu; Xueheng Zhuang; Guoguo Tan; Mingqiang Ning; Qikui Man (Chemical Engineering Journal, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Association of outdoor artificial light at night with mental health among China adults: a prospective ecology study - Zhenfan Yu; Naifan Hu; Yurun Du; Huihui Wang; Lining Pu; Xue Zhang; Degong Pan; Xiaoxue He; Jiangping Li (Environmental Science and Pollution Research, 2022)

Observations and modelling of the travel time delay and leading negative phase of the 16 September 2015 Illapel, Chile tsunami - Peitao Wang; Zhiyuan Ren; Lining Sun; Jingming Hou; Zongchen Wang; Ye Yuan; Fujiang Yu (Acta Oceanologica Sinica, 2021)

Cloning, characterization, and transcriptional activity of β-actin promoter of African catfish (Clarias gariepinus) - Sanghyok Ri; Wenho Hwang; Sangryong Ri; Wei Shi; Yu Han; Yu Tang; Lining Zhang; Maocang Yan; Guangxu Liu (Molecular Biology Reports, 2021)

Comparison of intrinsic water use efficiency between different aged Pinus sylvestris var. mongolica wide windbreaks in semiarid sandy land of northern China - Lining Song; Jiaojun Zhu; Qiaoling Yan; Mingcai Li; Guoqing Yu (Agroforestry Systems, 2015)

Water utilization of Pinus sylvestris var. mongolica in a sparse wood grassland in the semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Mingcai Li; Zhanyuan Yu (Trees, 2014)